Benham-McNeil family papers - Benham, Elizabeth Ann McNeil; Benham, Henry Washington, 1813-1884.; McNeil, John, 1784-1850.
Correspondence and other papers of Henry Washington Benham, Elizabeth Ann McNeil Benham, and John McNeil, relating chiefly to McNeil's service in the War of 1812 and Benham's career in the Army Corps of Engineers. Correspondents include Edward Everett Hale, George B. McClellan, Franklin Pierce, Thomas W. Sherman, and William T. Sherman.
Collection material in English.
Keywords: Hale, Edward Everett, -- 1822-1909 -- Correspondence; McClellan, George Brinton, -- 1826-1885 -- Correspondence; Pierce, Franklin, -- 1804-1869 -- Correspondence; Sherman, Thomas W. -- 1813-1879 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Benham family; McNeil family; United States. -- Army. -- Corps of Engineers; United States -- History -- War of 1812.